Real-farming emissions of reactive nitrogen – Necessities and challenges. (15th June 2019) - Sundrum, Albert
Abstract: Reactive nitrogen (Nr) is both a principal factor regulating growth in biological systems and a significant pollutant for the environment. The objective of this paper is to reflect on the challenges of the nutrient management related to and priorities needed to clarify how Nr is employed appropriately whilst striving to mitigate emissions at the same time. To create orientation, valid data are needed reflecting the real-farming emissions (RFE) from individual farms to assess what is needed to balance partly contradicting goals, and to bridge the gap between current and envisaged levels. Furthermore, knowledge is required of which tools and measures are at the farmer's disposal to mitigate Nr emissions. Finally and of utmost importance, the farm management is in need of action knowledge, i.e. knowing how to select the most appropriate and cost-effective tools and measures for the specific conditions on each farm, while taking the possible impacts of their implementation on the balance between Nr-related productivity and threats into account. Dealing with such a complex issue requires a systemic approach, considering the farm system not only as a one-compartment model (1st scale) with quantifiable Nr inputs and outputs at the farm gate but as divisible into sub-systems (2nd scale). The Nr-flow through the sub-systems: feed, livestock, manure and utilised land area, represents an inner-farm Nr-cycle. Each sub-system can be further sub-divided into sub-sub-systems (3rd scale) such as feeding groups within livestock, which could be differentiated in individual animals (4th scale). This approach enables to determine where (and to what extent) nutrients may be allocated more effectively and more cost-efficiently. The allocation of Nr resources between sub-units within the respective sub-systems determines the efficiency in the use of Nr and thus the proportion of Nr contributing either to an increase in productivity or to Nr-related environmental pollution. Quantifying the N-flows through sub-systems of a farm on the 2nd scale is the starting point for benchmarking; providing orientation for the regulation of processes both inside and outside the farm system. It creates target figures for the farm management while identifying the gap between the current ranking level of the farm and its potential rank. Improving the recycling of Nr throughout the whole farm system and increasing the efficiency in the use of Nr on the 3rd and 4th scale are seen as major opportunities for the farm management to balance the trade-offs without comprising productivity. It is concluded that the lack of benchmark RFE values in relation to the amount of food and feed produced can be seen as one of the main barriers in the fight to mitigate environmental Nr emissions from agricultural processes. If benchmarking has not been established, the farm management lacks orientation regarding the target figures it should aim at. Without target figures it is not possible to formulate concise working hypotheses regarding the most effective and cost-efficient use of means that are to the farmer's disposal as well as strategies for an improved allocation of resources in a farm specific context. Highlights: Use of Nr is facing trade-offs which have to be balanced within the farm systems. Understanding Nr losses and solving possible conflicts require a context-dependent approach. Quantification of Nr output/input ratios of sub-systems is essential for the nutrient management. Appropriate allocation of Nr resources require clear target figures based on benchmarking. Mitigation of Nr emissions while considering trade-offs is best achieved by increasing efficiency.